Khan Academy as a digital strategy for the development of mathematical thinking - Vélez Basurto, Erick Xavier (2024)
The modern Knowledge Society perceives an innovative characteristic based on managing curricular content, promoting logical mathematical thinking through digital platforms and applications. The objective of this work is focused on analyzing teaching strategies applied by teachers to enhance mathematical skills in students at the Unified General Baccalaureate level within the “Eidan Abel Erique Cercado” Educational Unit of the San Vicente canton. The methodological aspect was based on the mixed approach, using as a primary instrument a pedagogical test that measures numerical thinking skills, as well as the evidence of a semi-structured interview and the contributions of mathematics teachers as participants in a focus group. . The predisposition for work oriented under the Khan Academy platform was verified, necessary to benefit the student's poorly perfected numerical thinking skills. Finally, those strategies used by teachers were denoted which do not claim consistent stimulation to enhance numerical skills, demonstrated at a low acceptable level in strengthening problem solving with a mathematical focus in students.